The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1109/jlt.2014.2327140
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Constructions of Optical Codes With Large Cardinality and Multiple Tree Structures

Abstract: Algebraic optical codes with large cardinality and unique tree structures of multiple levels of subsets of codewords for adjustable code performance and cardinality have recently been proposed. As shown in this paper, these characteristics support new network architecture and applications for rapid code switching and physical-layer security in optical code-division multiple access networks. In addition, a new "translate" method of converting "additive" error-correction codes (ECCs) into this kind of optical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Because the optical codes in Section III and [13]- [16] are designed with each codeword using all available wavelengths at most once. Thus, codeword switching can be done all-optically by simply rearranging the wavelengths at different time slots, as illustrated in Fig.…”
Section: Applications Of Large-cardinality Tree-structured Opticmentioning
confidence: 99%
See 4 more Smart Citations
“…Because the optical codes in Section III and [13]- [16] are designed with each codeword using all available wavelengths at most once. Thus, codeword switching can be done all-optically by simply rearranging the wavelengths at different time slots, as illustrated in Fig.…”
Section: Applications Of Large-cardinality Tree-structured Opticmentioning
confidence: 99%
“…In [15] and [16], a new relationship between non-binary ECCs [22]- [26] and 2-D optical codes was established. It was shown that distinct 2-D optical codewords could also be generated from the "translated" copies (i.e., repeatedly adding the all-"1" codeword) of ECCs, instead of cyclic-shifted copies [13], [14].…”
Section: Constructions Of Mds-based Optical Codesmentioning
confidence: 99%
See 3 more Smart Citations